PRELIMINIRY RESULTS OF THE STUDY OF DENDROFLORA OF AKTOBE CITY (REPUBLIC OF KAZAKHSTAN) - Utarbayeva, N. A.; Aipeisova, S. A. (Acta Biologica Sibirica, 2016)
Dendroflora of Aktobe city consists of 71 species and forms belonging to 40 genera and 18 families. The predominant number of species are Rosaceae, Salicaceae, and Pinaceae. Their total participation in the dendroflora of Aktobe city is 56.3%. The basis of the city greening forms some 7 tree species: aspen, elm, smooth, rough, ash-leaved maple, yellow acacia, Syringa vulgaris. Among the bushes the most common are dog-rose bushes and cherry shrubs. During the research we revealed infectious diseases of trees and shrubs that have been identified. We registered 17 fungi species on 12 species of trees and shrubs. The most common diseases are powdery mildew, rust and spot, the most vulnerable tree species were Ulmus pinnato-ramosa, Acer negundo, Fraxinus pennsylvanica, Populus nigra.